Landslide hazard mapping and bio-engineering solutions for riverbank stabilization in the Cisanggarung River Basin, Indonesia: A GIS-based approach - Juniati, Atie Tri; Plamonia, Nicco; Ariyani, Dwi; Fitrah, Muhammad; Kuncoro, Dwi Agus (Brawijaya University, 2025)
Landslides along riverbanks pose significant risks to infrastructure, human safety, and environmental stability. This study used a GIS-based approach to map landslide hazards and implement bio-engineering solutions for riverbank stabilization in the Cisanggarung River Basin (CRB), Indonesia. The analysis incorporated multiple parameters, including slope, soil type, land use, and riverbank characteristics, to identify potential landslide-prone areas. Data from DEMNAS, soil type maps, and land cover maps were processed using GIS tools to generate a comprehensive landslide hazard map. The results indicated that the upper and middle sections of the Cisanggarung River are particularly vulnerable to landslides, with high-risk areas identified based on slope gradients and soil sensitivity. The study further evaluated the suitability of bio-engineering techniques, such as vegetation-based stabilization, to mitigate landslide risks. The proposed solutions were focused on the highest-risk points, which were determined through scoring analysis of the identified parameters. This research provides critical insights for local authorities and environmental planners, offering a practical framework for landslide risk management and sustainable riverbank restoration in the region.